2018
DOI: 10.17718/tojde.415837
|View full text |Cite
|
Sign up to set email alerts
|

Successful Students in an Open and Distance Learning System

Abstract: Learning in a higher education institution that applies an open and distance learning system requires the students to study as independent learners. This research is a survey research with the purpose of exploring the characteristics, habits and learning motivation of high-achiever students or those who obtained a high level of Grade Point Average (GPA). The sample used in this study was Universitas Terbuka (UT) students of Non Elementary Education Programs who had completed at least four semesters and had obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In general, the retention theory basically discusses the factors that influence student retention positively or negatively (Kinder et al, 2002). Several theoretical models of retention have been offered in both domains of traditional learning and DL (Bean & Metzner, 1985;Boshier, 1973;Boyles, 2000;Braxton et al, 1997;Frankola, 2001;Garland, 1993;Kember, 1981;Khan et al, 2018;Kinder et al, 2002;McEwen & Gueldenzoph, 2003;Morris & Finnegan, 2005;Puspitasri & Oetoyo, 2018;Tinto, 1975Tinto, , 1982Tinto, , 1993Sweet, 1986;Tillman, 2002;Traxler, 2018 Cabrera, Castaneda, Nora, and Hengstler (1992) pointed out that individual attrition from academic institutions can be ascribed to a longitudinal process of interactions between an individual and other members of the academic and social systems of the institution, herewith stressing the importance of individual factors and institutional involvement in attrition and retention research. Bean and Metzner (1985), on the other hand, considered attrition behaviour as a function of the person and his/her environment, and, given the fact that DL students do not regularly attend classes on campus, emphasized the need to take external environment factors into account, rather than so-called social integration variables that mainly affect traditional students on campus (Boyles, 2000).…”
Section: Review Of Literature On Student Attrition and Retentionmentioning
confidence: 99%
“…In general, the retention theory basically discusses the factors that influence student retention positively or negatively (Kinder et al, 2002). Several theoretical models of retention have been offered in both domains of traditional learning and DL (Bean & Metzner, 1985;Boshier, 1973;Boyles, 2000;Braxton et al, 1997;Frankola, 2001;Garland, 1993;Kember, 1981;Khan et al, 2018;Kinder et al, 2002;McEwen & Gueldenzoph, 2003;Morris & Finnegan, 2005;Puspitasri & Oetoyo, 2018;Tinto, 1975Tinto, , 1982Tinto, , 1993Sweet, 1986;Tillman, 2002;Traxler, 2018 Cabrera, Castaneda, Nora, and Hengstler (1992) pointed out that individual attrition from academic institutions can be ascribed to a longitudinal process of interactions between an individual and other members of the academic and social systems of the institution, herewith stressing the importance of individual factors and institutional involvement in attrition and retention research. Bean and Metzner (1985), on the other hand, considered attrition behaviour as a function of the person and his/her environment, and, given the fact that DL students do not regularly attend classes on campus, emphasized the need to take external environment factors into account, rather than so-called social integration variables that mainly affect traditional students on campus (Boyles, 2000).…”
Section: Review Of Literature On Student Attrition and Retentionmentioning
confidence: 99%
“…According to Puspitasari and Oetoyo (2018), student motivation is related to the learner's purpose to study. Possible reasons for opting to enroll in online courses are discussed in the literature.…”
Section: Individual Barriersmentioning
confidence: 99%
“…As a result, Puspitasari and Oetoyo (2018) suggested that institutions should offer guidance in planning and managing time in order to help students reconcile work/family and study responsabilities. Moreover, Park and Choi (2009) recommended that learners' family and organization should be apprised of the course advantages since students are more likely to withdraw from online courses when they perceive lack of family and organizational support.…”
Section: Individual Barriersmentioning
confidence: 99%
See 2 more Smart Citations